A phenomenological exploration of mental toughness in decision-making: Perceptions from professional Ghanaian footballers - Benjamin Asamoah; Adwoa Bemah Boamah Mensah; Heinrich Wilhelm Grobbelaar (PLoS ONE, 2026)
Mental toughness is an indispensable psychological resource facilitating performance excellence but its role in decision-making within African football remains underexplored. The current study explored and described professional Ghanaian footballers perceptions on the role of mental toughness in their decision-making. A descriptive phenomenological study design was adopted. A purposive sampling technique was used to recruit 12 male Ghana Premier League players who participated in semi-structured in-depth interviews. Transcribed interviews were analysed using Colaizzi’s framework to capture the essence of the participants’ lived experiences. Participants described mental toughness as a dynamic context-dependent resource that influence decision-making across five domains: strategic career development, performance-based, professional development, leadership and team oriented, and general life management. Mental toughness facilitated balancing professional obligations with cultural expectations. The study provides the first phenomenological account on how mental toughness shapes decision-making in Ghanaian football. It extends mental toughness conceptualisation beyond performance enhancement to life management and culturally embedded processes shaped by structural and social realities. These insights offer implications for talent development programmes and contextually informed psychological support interventions.